Islamic retail financing training implementation and impact: the case at Bank Kerjasama Rakyat Malaysia Berhad - Khairunnazlee, Mohd Noor (2024)
Islamic retail financing is the foundation of the development of Islamic banking since its employees were expected to be knowledgeable of Shariah-compliant products. It is crucial in this area to train employees well enough so that they can be very compliant and have better product knowledge. The purpose of this research is to explore the implementation and impact of Islamic Retail Financing Training in Bank Kerjasama Rakyat Malaysia Berhad. Additionally in this research, structured interviews have been conducted with ten respondents, they are the Centre of Excellence under People Sector head of management in training division in the bank, who hold different positions and participated in the interview sessions. These approaches have been adopted to assess employees’ knowledge of Islamic banking products. After interviewing the informants, the findings reveal a high significant positive correlation between the implementation Islamic retail financing training in the bank with several key outcomes contributing to the factors on the increasing in Islamic product knowledge among the bank’s employees, boosting in Islamic product sales of the bank, development of job competency of the bank’s employees and reduction in compliance issue such as common audit findings and Shariah non-compliance issue. The results suggest that the bank’s management should prioritize the enhancement of their employees’ knowledge of Islamic retail financing products. Offering specialized courses and structured training programs in Islamic banking can significantly improve employees' ability to apply these skills in practice. This study presents new insights into the area of Islamic banking product knowledge among Bank Kerjasama Rakyat Malaysia Berhad employees. The study developed valid constructs, and the identified themes were analyzed, demonstrating their impact on and influence over product knowledge